EXPERT SYSTEM APPLICATION TO DIAGNOSE ESCHERICHIA COLI (E-COLI) BACTERIA IN REFILLED DRINKING WATER USING THE CERTAINTY FACTOR METHOD - Rizky Fauziah (INFOKUM, 2021)
Sometimes many people do not know whether the water is suitable for consumption or not. The reason is because the water that is consumed daily without going through the cooking or boiling process first.Many of the depots that have sprung up today do not include a letter from the local health office stating that the drinking water sold is fit for consumption. Expensive costs and very difficult affairs make the owners of drinking water depots ignore the most important things that actually must be owned. One of the things that can threaten health through drinking water is the presence of Escherichia Coli (E-Coli) bacteria. To find out whether the drinking water that is consumed contains E-Coli bacteria is not easy, because its size is very small and invisible to the eye. One of the consequences that can be caused by E-Coli bacteria is abdominal pain, vomiting, diarrhea, high blood pressure, and even kidney disorders. Certainty Factor (certainty factor) expresses belief in an event or fact based on evidence or expert judgment. Certainty Factor uses a value to assume the degree of confidence of an expert on a data. Many studies get references to do further research with different problems. Where the certainty factor method solves a problem with the concept of belief and disbelief. So that it can be seen whether the certainty factor method can also be used in solving other problems. Where the certainty factor method solves a problem with the concept of belief and disbelief. So that it can be seen whether the certainty factor method can also be used in solving other problems. Where the certainty factor method solves a problem with the concept of belief and disbelief. So that it can be seen whether the certainty factor method can also be used in solving other problems.